(untitled) (Medico Legal Update, 2020)
Background : The decline of cognitive function is a problem that often experienced by the elderly. Objectives : to determine the role of elderly gymnastics towards cognitive function. Methods : A total of 50 elderly patients that fulfilled the inclusion and exclusion criteria in Kedurus village, Surabaya, from September to October 2013 were conducted. The cognitive function was examined using The Mini-Mental State Examination (MMSE) and the results were allocated to two groups: the case group with the MMSE score less than 26/30 while MMSE control group from 27/30. Results : During the study, 50 subjects were enrolled (25 case groups and 25 control groups). It was obtained in case group that did inactive-gymnastics was 15 (60%) and active-gymnastics was 10 (40%), with P = 0.047 and OR 3.188 (CI 0.99-10.17) Conclusion : There was no significant correlation between inactive-gymnastics elderly and active gymnastics towards cognitive function.